Nemzedéki orientációk instabil társadalmi környezetben - Gazsó, Ferenc (Szociológiai Szemle, 2024)
The paper draws a picture of how the changes of economic and social conditions in the course of systemic change have so far influenced the living conditions of the young generation as indicated by representative surveys done among them during the past four years. It is also presented what are their chances of schooling, professional training, and in the labour market, and how all these changes have modified the social mood, political attitudes and the reception of the unfolding new social set-up by the given generation. According to the unanimous experience of research the social mood of youth is dominated by a pessimistic sense of life. Drawn-out recession, massive unemployment, particularly hitting the young generation, the marketisation of education, the narrowing of the chances of mobility have created an unstable situation among the young generation. Youth regard themselves as one of the major losers of systemic change and sense their social position approaching the. living conditions of the lower strata under the most adverse conditions. Thus the Hungarian situation is characterised by growing generational tension, however, youth have not yet given up the hope in a personal future and in a positive change of the social and economic conditions. The paper, draws a comprehensive image of the sociological characteristics of a social set-up attractive to the youth, of the background of the negative assessment of the present state of affairs and of the interpretation of democracy evolved among the youth.